Reconstructing Criminal Asset Recovery in Indonesia's Digital Financial Crime: Integrating Criminal Liability, Digital Asset Tracing, and FATF Standards - Muhammad Ridwan Lubis; Rini Novita; Diana Lubis (Journal of Civil Criminal Law, 2026)
The rapid expansion of the digital economy, financial technology, cryptocurrencies, virtual assets, and blockchain has transformed financial transactions while simultaneously creating new opportunities for digital financial crime. Crimes such as online fraud, crypto-enabled money laundering, ransomware attacks, and cross-border illicit financial flows increasingly exploit technological innovations, making criminal asset recovery more complex. These developments expose significant weaknesses in Indonesia’s legal framework, particularly regarding the regulation of digital assets, tracing of criminal proceeds, and enforcement of effective recovery mechanisms. This study examines the shortcomings of Indonesia’s criminal asset recovery regime by analyzing the interaction between criminal liability, digital asset tracing, and compliance with Financial Action Task Force (FATF) standards. The research employs a doctrinal legal method using statutory, conceptual, comparative, case, and law reform approaches. The findings reveal that Indonesia’s regulatory framework remains fragmented and inadequately addresses the unique characteristics of cryptocurrencies and virtual assets. Regulatory inconsistencies, limited blockchain investigative capacity, weak beneficial ownership verification, fragmented institutional coordination, and incomplete alignment with FATF standards reduce the effectiveness of criminal asset recovery. Accordingly, this study proposes the Integrated Digital Asset Recovery Framework (IDARF), integrating criminal liability, blockchain-based asset tracing, beneficial ownership verification, FATF compliance, international cooperation, due process, human rights protection, and victim-oriented asset recovery. The proposed framework provides a normative foundation for legal reform through the enactment of a Digital Asset Recovery Act, the establishment of a Digital Asset Recovery Center, and strengthened institutional integration to improve Indonesia’s capacity to combat digital financial crime.